2000
DOI: 10.1016/s0009-2509(99)00314-0
|View full text |Cite
|
Sign up to set email alerts
|

Complex chemical reactions — A review

Abstract: Complex responses have been observed in a wide range of chemical and engineering systems: In well-stirred and unstirred solution-phase, in gels, in heterogeneous catalysis and dissolution reactions, in gas-and solid-phase combustion, widely in biological systems, accompanying phase transitions, in atmospheric kinetics and even in interstellar dust clouds. Complex behaviour does not, however, imply a necessarily complex underlying chemical mechanism. The appropriate feedback mechanisms, built on chainbranching,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Periodic travelling waves (PTWs) are a fundamental solution form in oscillatory reaction-diffusion equations, by which I mean reaction-diffusion systems whose kinetics have a stable limit cycle. PTWs are the one-dimensional analogue of spiral waves and target patterns, and underlie many observed behaviors in biology and chemistry (Bjørnstad, Ims, and Lambin (1999); Scott et al (2000)). In 1973, Kopell and Howard published their seminal paper, which showed that a reaction-diffusion system develops a one-parameter family of PTWs as its kinetics pass through a Hopf bifurcation.…”
mentioning
confidence: 99%
“…Periodic travelling waves (PTWs) are a fundamental solution form in oscillatory reaction-diffusion equations, by which I mean reaction-diffusion systems whose kinetics have a stable limit cycle. PTWs are the one-dimensional analogue of spiral waves and target patterns, and underlie many observed behaviors in biology and chemistry (Bjørnstad, Ims, and Lambin (1999); Scott et al (2000)). In 1973, Kopell and Howard published their seminal paper, which showed that a reaction-diffusion system develops a one-parameter family of PTWs as its kinetics pass through a Hopf bifurcation.…”
mentioning
confidence: 99%
“…We do not model the very high latitude region. As follows from Johnson et al (1998) and Scott et al (2000), two-day oscillations in this region are suppressed for real values of horizontal eddy diffusion coefficient.…”
Section: Modelmentioning
confidence: 82%
“…The concentrations of Br 2 and CO 2 oscillate without an induction period in this system, and it is necessary to bubble an inert gas such as N 2 through the reaction mixture in order to observe oscillations. This behaviour may be explained by including bromine hydrolysis, a rate of removal of Br 2 (24), and steps (25) and (26) to the FKN:…”
Section: (Ii)mentioning
confidence: 99%
“…The scientific activity associated with this reaction is still strong, and it remains a useful way of testing nonlinear kinetic theory [23]. It is undoubtedly the most extensively studied oscillating chemical reaction [24][25][26][27]. This review will focus primarily on the BZ reaction; however, reference to other reactions will be made where appropriate.…”
mentioning
confidence: 99%